2014
DOI: 10.1177/0954410014547441
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of turbulent Prandtl/Schmidt number in compressible mixing layer

Abstract: The behaviour of turbulent Prandtl/Schmidt number is explored through the model-free simulation results. It has been observed that compressibility affects the Reynolds scalar flux vectors. Reduced peak values are also observed for compressible convective Mach number mixing layer as compared with the incompressible convective Mach number counterpart, indicating a reduction in the mixing of enthalpy and species. Pr t and Sc t variations also indicate a reduction in mixing. It is observed that unlike the incompre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…A few researchers [32][33][34][35] have suggested use of complicated additional transport equations for the modeling of turbulent Prandtl/Schmidt numbers in the propulsive flows. The researchers [36] have carried out model free simulations for compressible and incompressible mixing layers and shown that the turbulent Prandtl/Schmidt numbers do not vary significantly for incompressible cases while observing a continuous variation of these numbers in compressible cases. Many numerical studies [37][38][39] carried out for subsonic combustor performance, have also shown that assumption of constant turbulent Prandtl/Schmidt numbers can give good prediction of the flow variables.…”
Section: Governing Equations and Modelsmentioning
confidence: 98%
“…A few researchers [32][33][34][35] have suggested use of complicated additional transport equations for the modeling of turbulent Prandtl/Schmidt numbers in the propulsive flows. The researchers [36] have carried out model free simulations for compressible and incompressible mixing layers and shown that the turbulent Prandtl/Schmidt numbers do not vary significantly for incompressible cases while observing a continuous variation of these numbers in compressible cases. Many numerical studies [37][38][39] carried out for subsonic combustor performance, have also shown that assumption of constant turbulent Prandtl/Schmidt numbers can give good prediction of the flow variables.…”
Section: Governing Equations and Modelsmentioning
confidence: 98%